Review articlesManagement of chronic hand eczema - Batycka-Baran, Aleksandra; Baran, Wojciech; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Hand eczema (HE) is a common dermatological condition with a prevalence of about 10% in the general population. It is also the most common occupational skin disorder. The disease is caused by multiple factors, most often irritants and contact allergens. Hand eczema varies because of aetiology and morphology of skin lesions. It often has a chronically relapsing course resulting in a high social and economic impact for the individual. Although different treatment options exist, long remission is hard to achieve. As known from the literature, very few randomized controlled trials exist to provide evidence-based recommendations for therapy of this disorder. Hope for better management of patients with chronic HE is provided by new drugs, e.g. alitretinoin, whose efficacy and safety have been confirmed in recently published clinical trials.